Use of urinary hydroxyproline excretion as a marker of bone metastases in prostatic cancer (1) - Kurokawa, K (Hinyokika kiyo. Acta urologica Japonica, 1985)
Twenty-four hour urinary hydroxyproline and urinary hydroxyproline creatinine ratio was measured without prior dietary restriction in 24 patients with prostatic cancer and 16 patients with benign prostatic hypertrophy. Both were elevated in patients with prostatic cancer with active bone metastases compared to the values of prostatic cancer without bone metastasis and benign prostatic hypertrophy. In these cases, the values of urinary hydroxyproline creatinine ratio were more reliable. The results show that urinary hydroxyproline creatinine ratio is a very sensitive indicator of active bone metastases of prostatic cancer without dietary restriction